TANGGAPAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) TERHADAP PEMBERIAN BIOCHAR DAN PUPUK HAYATI PADA TANAH GAMBUT (Response of Tomato Plant (Lycopersicum esculentum Mill) to The Application of Biochar and Biofertilizer on Peat Soil.) - Y., Alianti; S., Zubaidah, S.; D., Saraswati, D. (Universitas Palangka Raya, 2016)
response of tomato cropâs growth and yield due to application ofbiochar and biofertilizer on peat soil. This research utilized Completely Randomized Design with twofactors. The first factor was the application of biochar (B) that was consisted of 4 levels : B0 = control,B1 = 2 t.ha-1 , B2 = 4 t.ha-1 and B3 = 6 t.ha-1. The second factor was the application of biofertilizer (M)that was consisted of 3 levels : M0 = control, M1 = 1 t.ha-1 , M2 = 2 t.ha-1. Variables observed were cropheight, number of leaf, dry weight of crop, number of fresh harvested fruit and weight of freshharvested fruit. Results showed that there was an interaction between the application of biochar andbiofertilizer that affected the number of leaf, the dry weight of crop, the number of fresh harvested fruitand the weight of fresh harvested fruit. Interaction between those treatments did not have anysignificant effect on crop height and it is only affected each single factor. Best response of tomatocropâs growth and yield on peat soil was to the application of 6 t.ha-1 biochar and 2 t.ha-1 biofertilizer(B3M2), in which the average weight of fresh harvested fruit was 734,6 g/plant.Keywords: tomato, biochar, Biofertilizer, Peat SoilABSTRAK